1998
DOI: 10.1016/s1097-2765(00)80071-4
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the N-Terminal Domain of Sialoadhesin in Complex with 3′ Sialyllactose at 1.85 Å Resolution

Abstract: The structure of the functional N-terminal domain from the extracellular region of the cell surface receptor sialoadhesin has been determined in complex with the oligosaccharide 3' sialyllactose. This provides structural information for the siglec family of proteins. The structure conforms to the V-set immunoglobulin-like fold but contains several distinctive features, including an intra-beta sheet disulphide and a splitting of the standard beta strand G into two shorter strands. These novel features appear im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
283
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(301 citation statements)
references
References 56 publications
18
283
0
Order By: Relevance
“…25): (i) the N-terminal region leading to the ␤-strand A; (ii) loop C-CЈ; (iii) loop CЈ-D; and (iv) the ␤-strand F, which harbors the essential arginine. Of these, regions i, ii, and iv may be relevant to glycan recognition, as suggested by previous in vitro mutagenesis studies (25,29,30). This result suggests that rapid evolution of the Ig1 of CD33rSiglecs may be related to the modification of these molecules to accommodate ongoing changes in host sialylation patterns.…”
Section: Rapid Accumulation Of Nonsynonymous Substitutions In the Firstsupporting
confidence: 52%
“…25): (i) the N-terminal region leading to the ␤-strand A; (ii) loop C-CЈ; (iii) loop CЈ-D; and (iv) the ␤-strand F, which harbors the essential arginine. Of these, regions i, ii, and iv may be relevant to glycan recognition, as suggested by previous in vitro mutagenesis studies (25,29,30). This result suggests that rapid evolution of the Ig1 of CD33rSiglecs may be related to the modification of these molecules to accommodate ongoing changes in host sialylation patterns.…”
Section: Rapid Accumulation Of Nonsynonymous Substitutions In the Firstsupporting
confidence: 52%
“…These results suggest that there may be two independent sites for binding sialic acid on MAG as suggested previously by others (26,64,65) from analysis of MAG binding to ganglioside ligands. This conclusion was also reached by Vinson and co-workers (22,60,66) who mutated the conserved Arg-118 essential for sialic acid binding in sialoadhesin and found that MAG still mediated sialic aciddependent effects on neurite outgrowth (67).…”
Section: Potent Inhibition Of Mag (Siglec-4) By O-linked Sialosides-tomentioning
confidence: 55%
“…More approachable has been the analysis of the specificity of siglecs to the sialoside sequence itself. The crystal structure for the sialoadhesin V-set domain with bound 3Ј-sialyllactose (NeuAc␣(2-3)Gal␤(1-4)Glc) revealed that sialoside binding is stabilized predominantly by contacts with the sialic acid, including a salt bridge between the C-2 carboxyl group and a highly conserved Arg at residue 97 (22). Yet numerous reports have documented that the siglecs differ in their specificity toward other elements of sialoside sequences (2,3).…”
mentioning
confidence: 99%
“…MOG is structurally similar to other IgV domains such as the peripheral nerve system protein P zero (27), the IgV domains of the ␥␦-T cell receptor (28), and various variable antibody domains. The nearest structural neighbors of MOG are the N-terminal domains of the costimulatory molecule B7-2 (29) (CD86) and sialoadhesin (30), which superimpose with MOG with rms deviations of 1.18 and 1.37 Å for 97 and 100 aligned C ␣ atoms, respectively.…”
Section: Resultsmentioning
confidence: 99%